Diagnostics of Amyotrophic Lateral Sclerosis: Up to Date - Štětkářová, Ivana; Ehler, Edvard (Diagnostics (Basel, Switzerland), 2021)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease characterized by gradual loss of upper and lower motor neurons and their pathways, usually without affecting the extraocular and sphincter muscles. The cause of the disease is not yet known. It is a chain of subsequent events, ending in programmed cell death in selective neuronal subpopulations. The prognosis for survival is rather short with a median of 2 to 4 years. Survival may be prolonged based on prompt diagnosis, ALS subtype and proper management with supportive treatment (tracheostomy, gastrostomy, etc.). According to the clinical picture, the typical form of ALS with upper and lower motoneuron involvement and progressive bulbar paralysis with bulbar muscle involvement is observed. The ALS form with progressive muscle atrophy, where only the lower motoneuron is affected, and primary lateral sclerosis with only upper motoneuron damage are rare. Familiar forms of ALS (FALS) associated with specific genes (the most common is C9orf72) have been discovered. FALS is usually associated with dementia (frontotemporal lobar dementia, FTLD), behavioral disorders, cognitive dysfunction and impairment of executive functions. The diagnosis of ALS is determined by excluding other conditions and utilizing clinical examinations, laboratory and genetic tests and nerve conduction/needle electromyography studies (EMG). Needle EMG records abnormal activities at rest and looks for neurogenic patterns during muscle contraction. Motor evoked potentials after transcranial magnetic stimulation remain the test of choice to identify impairment of upper motor neurons. New biochemical, neurophysiological and morphological biomarkers are extensively studied as early diagnostic and prognostic factors and have implications for clinical trials, research and drug development.
Keywords: electromyography; amyotrophic lateral sclerosis; biomarkers; diagnostics; ALS; FTLD